Factor investing : from traditional to alternative risk premia - Jurczenko, Emmanuel (Quantitative finance set, 2017)
This new edited volume consists of a collection of original articles written by leading industry experts in the area of factor investing. The chapters introduce readers to some of the latest research developments in the area of equity and alternative investment strategies. Each chapter deals with new methods for constructing and harvesting traditional and alternative risk premia, building strategic and tactical multifactor portfolios, and assessing related systematic investment performances. This volume will be of help to portfolio managers, asset owners and consultants, as well as academics and students who want to improve their knowledge and understanding of systematic risk factor investing.